Effect of Skin-to-Skin Care on the Day of Birth on Skin Colonization in Preterm Infants: A Pre- and Post-Implementation Study - Poorva Deshpande; Nosheen Akhtar; Maura Mansur; Allison McGeer; Vibhuti Shah (Children)
Background/Objectives: Maternal skin-to-skin contact (MSSC) in neonates has been shown to reduce nosocomial infections. In preterm infants, exposure to maternal skin commensals within the first 24 h may prevent colonization by hospital-acquired pathogens. However, the impact of early MSSC on skin colonization in preterm infants is unknown. Our aim was to compare skin colonization patterns on days 2, 3, and 7 of life in preterm infants (280/7 to 316/7 weeks gestational age) who received MSSC within the first 24 h from birth with those who did not. The primary outcome was the rate of skin colonization with bacterial pathogens. The secondary outcome was the rate of Staphylococcus aureus colonization. Methods: This prospective pre- and post-implementation study was conducted at Mount Sinai Hospital, Toronto. Skin swabs were obtained at 24–36 h, 48–72 h, and day 7 of life. Infant mouth and rectal swabs were collected on day 7. Maternal nasal–rectal swabs were obtained at any time from recruitment to day 7. Results: Twenty-seven infants were included in the pre-implementation group and seventeen were included in the post-implementation group, respectively. Post-implementation infants received an increased duration of SSC during the first week. No differences in colonization with pathogens vs. commensals or Staphylococcus aureus colonization were observed between groups at any time point. Skin was fully colonized in both groups by day 7. Conclusions: No differences in skin colonization patterns were identified in the first week of life for preterm infants receiving early MSSC. Larger studies with longitudinal data are needed to further evaluate the impact of MSSC on skin colonization.